Proliferative activity in melanocytic nevi from patients grouped by age with clinical follow‐up. (17th November 2015) - Lu, Dongsi; Levin, Ethan C.; Dehner, Louis P.; Lind, Anne C.
Abstract : Any mitotic activity in a melanocytic nevus is a source of concern about the biologic potential of that lesion, especially in an adult. Previously diagnosed benign melanocytic nevi in individuals from six different age groups were re‐examined; mitotic figures were counted in routine hematoxylin and eosin‐stained sections; Ki‐67 nuclear positivity was assessed by immunohistochemistry. Mitoses were seen in 0–14.3% of nevi in all groups of patients >1 year of age; 55.6% (5/9 cases) of nevi in patients <1‐year old had mitoses identified histologically. Ki‐67‐positive melanocytes were seen in all cases of those lesions in infants (less than 1‐year old) and only in a minority of lesions from the other age groups. The maximum and mean numbers of Ki‐67‐positive melanocytes per square millimeter were highest in patients <1‐year old (16.7 and 5.6, respectively), and decreased in all other groups. Follow‐up data were available in the majority of the patients. There were no examples of malignant melanoma in the various age groups. We conclude that proliferative activity in benign melanocytic nevi decreases with age, however, proliferative activity can be seen at any age and its significance must be judged in the context of other histopathologic features.